Research methods in public administration and public management an introduction - Thiel, Sandra van (Routledge masters in public management series, 2014)
"Research Methods in Public Administration and Public Management represents a comprehensive guide to doing and using research in public management and administration. [... It covers] a wide variety of research strategies including among others: action research, hypotheses, sampling, case selection, questionnaires, interviewing, desk research, prescription and research ethics"--Publisher